Sufis, sultans, and feudal orders : Professor Nurul Hasan commemoration volume - Haidar,Mansura Ed (Manohar, 2004)
Contributed articles honoring Professor Nurul S. Hasan, b. 1921, on Indian history in medieval period, during 14th to 19th century and sufism; also includes some memoirs on him.